Structural characterization of the n = 5 layered perovskite neodymium titanate using high-resolution transmission electron microscopy and image reconstruction. - Sayagués, M; Titmuss, K; Meyer, R; Kirkland, A; Sloan, J; Hutchison, J; Tilley, R (2003)
The structure of Nd(5)Ti(5)O(17) has been refined from a reconstruction of the specimen exit-plane wave restored from a series of incrementally defocused high-resolution transmission electron microscope (HRTEM) images. The phase of the exit-plane wave shows contrast attributable to the oxygen anion sublattice and coupled with simulations provides confirmation of the composition of the cation sites as a function of sample thickness. The enhanced resolution in the exit-plane wave additionally allows a direct measurement of the 'skewing' of the perovskite slabs.